Right ventricular free wall dissection as a rupture tract in left ventricular rupture during acute myocardial infarction. Issue 6 (November 2015) - Takada, Aya; Saito, Kazuyuki; Murai, Tatsuya; Kurosaki, Kunihiko; Kurihara, Katsuyoshi; Hamamatsu, Akihiko
Highlights: Right ventricular dissection rarely develops during acute myocardial infarction. The rupture tract dissects the superficial and the deeper layers of the myocardium. Delayed epicardial rupture could occur in the right ventricular dissection. Abstract: Three rare cases of cardiac rupture with right ventricular wall dissection during acute myocardial infarction (AMI) were reported. The cases comprised 2% among our 148 previously reported postinfarction cardiac ruptures with sudden death. The dissections occurred in hearts with biventricular inferior wall AMI and developed between the superficial layers and the deeper layers of inferior wall of the right ventricle. All had an endocardial tear at the basal septum where it meets the inferior free wall of the left ventricle, and had an epicardial tear on the middle inferior wall of the right ventricle. Based on the evidence of the ages of the thrombi of the rupture tracts, delayed epicardial rupture was found besides that soon after the right ventricular dissection.